Information and Communications Security : 18th International Conference, ICICS 2016, Singapore, Singapore, November 29 - December 2, 2016, Proceedings /: 18th International Conference, ICICS 2016, Singapore, Singapore, November 29 - December 2, 2016, Proceedings. ([2016]) - Unknown
No abstract available